Learning science using visualization: 3D animation / Jasni Alif Aminuddin Abdullah - Abdullah, Jasni Alif Aminuddin (2016)
Most of students did not get an 'A' in science in PT3 in year 2014 due to changes in exam format and also lack of interest in science subject. Furthermore, this subject require a lot of memorization. In order to help students, become more interested in learning science, this project is developed using combination of multimedia elements such as videos, animations, sounds, graphics and texts. With the implementation of the 3D element, it helps student to feel like real things with 3D objects. The development of this learning tools based on ADDIE model phases and cognitive learning strategy. This project has been tested by group of PT3 students and it showed that using this learning tools can increase their interest in learning science subject. By doing this research, I hope students have interest and learn science diligently. We can learn into deep with science and using evidence not just about learning. Furthermore, science give impact on the environment or making decision for our health care in daily lives.